Neisseria gonorrhoeae antimicrobial resistance patterns and associated risk factors in women of childbearing potential in northwestern Ethiopia - Engdawork Demissie; Azanaw Amare; Muluken Birhanu; Mucheye Gizachew (BMC Women's Health, 2024)
Abstract Backgrounds Neisseria gonorrhoeae causes gonorrhea and poses public health problems, including antimicrobial resistance. Current data on gonorrhea in prenatal participants in the study area are required. Thus, we aimed to identify gonorrhea prevalence, antimicrobial resistance, and risk factors among antenatal care clinic visitors in northwestern Ethiopia. Methods A cross-sectional study was conducted from March to August 2022 at the University of Gondar Comprehensive Specialized Hospital. We recruited 278 study participants using convenient sampling techniques. Sociodemographic, clinical and behavioral risk factors were recorded using pre-tested questionnaires. Endocervical swabs were collected by a physician, transported to the microbiology laboratory, immediately inoculated into modified Thayer-Martin medium, and it was incubated at 37 °C for 24–48 hours. Gram staining and biochemical tests were used to identify the organism. AMR testing was performed using disc diffusion and E-test methods. Data were entered in EPI-info version 7 and exported and analyzed in SPSS version 26. A p-value ≤0.05 was considered as statistically significant. Results were presented in words, tables and figure. Results Of 278 subjects enrolled, majority (44.6%) were 26–35 years, with a mean age of 29.9 (SD = ±7.2) years, 69.4% were urban residents, and 70.5% were married. Twenty-one (7.6%) participants had gonorrhea. Overall antimicrobial resistance ranged from 19 to 100%. High resistant to tetracycline (100%) and penicillin (85.7%) were observed by both tests. Ciprofloxacin resistance was 52.4% by disc diffusion and 85.7% by E-test. By E-test, all isolates were sensitive to ceftriaxone, cefixime, azithromycin and spectinomycin; however, 7 (33.3%), 9 (42.9%), 9 (42.9%) and 5 (23.8%) isolates showed resistant to these antibiotics with disk method. Prevalence of beta-lactamase producing Neisseria gonorrhoeae was 85.7%. Alcohol consumption (p = 0.032), condom-free sexual practice (p = 0.010), multiple sexual partners (p < 0.001), pelvic pain (p = 0.018), and dysuria (p = 0.021) revealed increased risk of infection. Conclusions Compared with many previous studies in Ethiopia, we found high prevalence, antimicrobial resistance, and beta-lactamase-positive isolates. Multiple sexual partners, alcohol consumption, not using condom, pelvic pain and dysuria were predictors of this infection. Continuous large-scale monitoring of pathogen is essential for its prevention and control.